Pengaruh Minat dan Kedisiplinan Terhadap Prestasi Belajar Siswa Kelas Tinggi SDN Gesi 1 Tahun Ajaran 2015 / 2016 - Fradiyati, Sulfa; , Drs. Saring Marsudi, SH. M.Pd (2015)
This study aims to determine the effect of interest on learning achievement, discipline influence on learning achievement, the effect of interest and discipline on student achievement high grade SDN Gesi 1. This study was included in the descriptive quantitative research with a conclusion through statistical analysis. The study population was all students of high grade (IV, V, VI) SDN Gesi 1 totaling 109 students. The research sample totaled 45 students. The technique of collecting data using questionnaires, interviews and documentation. Data were analyzed using multiple linear regression analysis, t test, F test, the coefficient of determination, SR, SE, preceded by analysis prerequisite test is a test of normality and linearity test. Based on the analysis of multiple linear regression equation: Y = 41.213 + 0,207X1 + 0,250X2. The results of data analysis with significance level of 5% was obtained : (1) Interest effect on student achievement. It is based on t test known that t count > t table, namely 2.402 > 2.017 and the significance value < 0.05 is 0.21 with the relative contribution of 49.1% and the effective contribution of 19.6%. (2) Disciplinary effect on student achievement. It is based on t test known that t count > t table is 2.471 > 2.017 and the significance value < 0.05 is 0.18 with the relative contribution of 50.9% and the effective contribution of 20.6%. (3) Interest and discipline effect on student achievement. This is based on F test known that Fcount > Ftable is 14,250> 3.23 and a significance value < 0.05 is 0.000. Based on the calculation coefficient of determination is known that the effect of the interest and discipline to student achievement contributed 40.4%, while 59.6% are influenced by other factors not examined. Keywords: Interest, Discipline and Achievement